Child and family-focused interventions for child maltreatment and domestic abuse: development of core outcome sets. Issue 9 (19th September 2022) - Powell, Claire; Feder, Gene; Gilbert, Ruth; Paulauskaite, Laura; Szilassy, Eszter; Woodman, Jenny; Howarth, Emma
Abstract : Background: The current evidence for child maltreatment (CM) and domestic violence and abuse (DVA) interventions is limited by the diversity of outcomes evaluated and the variety of measures used. The result is studies that are difficult to compare and lack focus on outcomes reflecting service user or provider priorities. Objective: To develop core outcome sets (COSs) for evaluations of child and family-focused interventions for: (1) CM and (2) DVA. Design: We conducted a two-stage consensus process. Stage 1: a long list of candidate outcomes across CM and DVA was developed through rapid systematic reviews of intervention studies, qualitative and grey literature; stakeholder workshops; survivor interviews. Stage 2: three-panel, three-round e-Delphi surveys for CM and DVA with consensus meetings to agree with the final COSs. Participants: 287 stakeholders participated in at least one stage of the process (ie, either CM or DVA COS development): workshops (n=76), two e-Delphi surveys (n=170) and consensus meetings (n=43). Stakeholders included CM and DVA survivors, practitioners, commissioners, policymakers and researchers. Results: Stage 1 identified 335 outcomes categorised into 9 areas and 39 domains. Following stage 2, the final five outcomes included in the CM-COS were: child emotional health and well-being; child's trusted relationships; feelings of safety; child abuse and neglect; service harms. The final five outcomes in the DVA-COS were: child emotional health and well-being; caregiver emotional health and well-being; family relationships; freedom to go about daily life; feelings of safety. Conclusions: We developed two COSs for CM and DVA with two common outcomes (child emotional health and well-being; feelings of safety). The COSs reflect shared priorities among service users, providers and researchers. Use of these COSs across trials and service evaluations for children and families affected by CM and DVA will make outcome selection more consistent and help harmonise research and practice.